Polarization and Its Discontents : Morocco Before and After the Arab Spring - Clementi, Fabio; Khan, Haider A.; Molini, Vasco; Schettino, Francesco; Soudi, Khalid (World Bank, Washington, DC, 2019)
This paper uses data obtained from three Moroccan household surveys that took place between 2000 to 2013, to address issues related to the so-called "Arab puzzle." Welfare inequalities are low and declining in Arab countries and exist against the backdrop of a growing sense of dissatisfaction and frustration. The paper hypothesizes that welfare inequality plays a role, if seen through the lens of absolute measures and notably absolute polarization. The paper argues that the relatively worse perception of poor, vulnerable, and lower middle-class Moroccan households mirrors the ongoing hollowing out of the welfare distribution process and its concentration in the tails. The results of a multi-logit regression indicate that polarization is significantly correlated to perception and, importantly, that this correlation is asymmetric. The poorer are the households, the more polarization is perceived to link negatively to the well-being of households; and the richer are the households, the more polarization will positively correlate with their perceived well-being. The results are robust to the use of classes or quintiles for ranking social groups from the poorest to the richest.